Length of stay in the pediatrics emergency department and associated factors among pediatrics patients in Eastern Ethiopia public hospital, Ethiopia 2022. - Netsanet Melkamu; Amelmasin Faris; Muluken Yigezu; Mickiale Hailu; Anteneh Atle; Manaye Kasahun; Mohammed Kebede; Tsegasew Embiale; Tsinukal Tesfay; Sewmehone Amsalu; Yakob Tadese; Bruck Tesfaye; et al. (PLoS ONE)
Introduction Patient length of stay is a crucial measure of the emergency department, and it is a vital indicator of health services to evaluate its efficacy, patient care, organizational management, and health care system. Despite this, there are a few studies conducted on pediatric emergency length of stay in developing countries. Therefore, this study serves as input for evidence of pediatric emergency length of stay and associated factors in public hospitals. Methods An institution-based cross-sectional study was conducted among children who attended in pediatric emergency department of Eastern Ethiopia public hospital from May 01 to Jun 31, 2022. A total of 761 children were selected by systematic sampling technique and interview using structured questionnaires. After data is collected and cleaned, entered using Epi data version 4.6 and then exported to Stata version 14.1 for analysis. Finally, an AOR with a 95% CI was computed, and variables with a P-value < 0.05 in the multivariable analysis were taken as significant factors for prolonged length of stay. Result The prevalence of prolonged length of stay in the emergency ward was 214 (72%). Living in a rural residence ([AOR = 1.65, 95% CI (1.10-2.48)], having a duration of pain > = 12 ([AOR = 1.92, 95% CI (1.13-3.25)], waiting time > = 5 minute ([AOR = 2.24, 95% CI (1.1-4.248541)], having comorbid illness ([AOR = 1.92, 95%CI, 1.13-3.25)], and higher acuity level and absence of medication in the hospital were ([AOR = 2.26, 95%CI (1.02-2.46]) were significantly associated factors for prolonged length of stay. Conclusion and recommendation This study revealed that more than two-thirds of children admitted to pediatric emergency had prolonged lengths of stay. This result indicated that higher proportion of the length of stay in pediatric emergency in Eastern Ethiopian public hospitals compare to national. Hence, it is better to give priority to strengthening the focused evaluation of important variables and manage accordingly.